Interactive learning in Python - Munmit Singh Dhillon (Nanyang Technological University, 2021)
The goal of the project is to identify the most efficient learning method for students. Sparkology is a prototype of a web-based learning management system that is focused on providing the best possible learning experience for its users in the realm of coding with Python, additionally, it serves as the platform to conduct the experiment of the effectiveness of learning styles. Sparkology focuses on novice programmers who do not have a foundation in programming. As every student has different learning methods, Sparkology adopts a different approach than traditional education methods.